Meristem Initiation and de novo Stem Cell Formation - Nicolas, Antoine; Laufs, Patrick (Frontiers in Plant Science, 2022)
Plant aerial development relies on meristem activity which ensures main body plant axis development during plant life. While the shoot apical meristem (SAM) formed in the embryo only contributes to the main stem, the branched structure observed in many plants relies on axillary meristems (AMs) formed post-embryonically. These AMs initiate from a few cells of the leaf axil that retain meristematic characteristics, increase in number and finally organize into a structure similar to the SAM. In this review, we will discuss recent findings on de novo establishment of a stem cell population and its regulatory niche, a key step essential for the indeterminate fate of AMs. We stress that de novo stem cell formation is a progressive process, which starts with a transient regulatory network promoting stem cell formation and that is different from the one acting in functional meristems. This transient stage can be called premeristems and we discuss whether this concept can be extended to the formation of meristems other than AMs.